2020
DOI: 10.1038/s41419-020-02798-y
|View full text |Cite
|
Sign up to set email alerts
|

Developmental demands contribute to early neuromuscular degeneration in CMT2D mice

Abstract: Dominantly inherited, missense mutations in the widely expressed housekeeping gene, GARS1, cause Charcot-Marie-Tooth type 2D (CMT2D), a peripheral neuropathy characterised by muscle weakness and wasting in limb extremities. Mice modelling CMT2D display early and selective neuromuscular junction (NMJ) pathology, epitomised by disturbed maturation and neurotransmission, leading to denervation. Indeed, the NMJ disruption has been reported in several different muscles; however, a systematic comparison of neuromusc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 74 publications
(126 reference statements)
3
28
1
Order By: Relevance
“…The Gars C201R/ + mice, which model CMT2D, presented a mild denervation phenotype associated with pre-synaptic and post-synaptic structural NMJ changes at 1 month of age: ~ 80% of hindpaw lumbrical NMJ were fully innervated, consistent with a recent report 73 . At this age, the ‘integrity’ parameter, which measures fragmentation and clusterization of nerve terminals and endplates, was increased on average while parameters quantifying size (volume, length, surface) were significantly decreased compared to WT littermates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The Gars C201R/ + mice, which model CMT2D, presented a mild denervation phenotype associated with pre-synaptic and post-synaptic structural NMJ changes at 1 month of age: ~ 80% of hindpaw lumbrical NMJ were fully innervated, consistent with a recent report 73 . At this age, the ‘integrity’ parameter, which measures fragmentation and clusterization of nerve terminals and endplates, was increased on average while parameters quantifying size (volume, length, surface) were significantly decreased compared to WT littermates.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with a previous report that endplate area of 1- and 3-month old Gars C201R/ + mice was 9% and 12% less than WT, respectively, although this did not reach significance 10 . A combination of delayed NMJ development, aberrant interaction between glycyl-tRNA synthetase (GlyRS) and the tropomyosin kinase receptor (TrK) receptors (some of which are found at the NMJ) and differential muscle involvement, all appear to contribute to the Gars C201R/ + mouse phenotype 10 , 73 , 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the cause, experiments presented here highlight the importance of comparative anatomy in mouse models of neuromuscular disorders to enhance understanding of pathomechanisms. It remains to be seen whether such variations are also observed in the motor nervous system of CMT2D mice, although differential susceptibility of muscles to NMJ denervation has been previously reported (Seburn et al, 2006;Sleigh et al, 2014bSleigh et al, , 2020Spaulding et al, 2016).…”
Section: Discussionmentioning
confidence: 90%
“… 27 , 43 Recently, a comprehensive study in Gars C201R/+ mutant showed that impaired NMJ maturation as an early defect preceded the loss of presynaptic terminals, leading to muscle denervation. 47 In this study, we introduced NT-3 gene transfer to Gars P278KY/+ mice representing a severe phenotype at 4–6 weeks of age and to Gars ΔETAQ/+ mice with a milder phenotype at 8–10 weeks of age and carried out a qualitative and quantitative assessment of NT-3 effect on the neuromuscular system 12 and 30 weeks post gene delivery, respectively. The treatment efficacy was less pronounced in the Gars ΔETAQ/+ mutant despite a prolonged efficacy period; although it remains to be seen if the outcome measures can be improved with early onset treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, these myopathic changes in Gars mutants have a striking resemblance to the muscle pathology described in SMA mouse models resulting from SMN reduction in muscle including the early NMJ breakdown. 47 , 61–63 In one study, myopathy occurred as a late-onset, cell-autonomous consequence of low SMN in muscle, which was also associated with functional and structural defects in NMJs despite normal levels of SMN in other tissues. 61 These observations warrant further studies exploring whether SMN levels are affected by a globally repressed protein synthesis in the Gars P278KY/+ mutant.…”
Section: Discussionmentioning
confidence: 99%